A Press Clause Right to Cover Protests - Tyler Valeska (Washington University Journal of Law & Policy, 2021)
As protests have become more frequent, an increasing number of journalists have been targets of harassment and violence. The long-disputed role of the First Amendment’s press clause demands attention now more than ever. This Article demonstrates how a theoretical framework for a revitalized press clause can be operationalized in a particular context: journalists covering protests. Valeska first details the normative and structural justifications for an affirmative press clause right to cover protests. He then considers two proposals for deciding whom the right would protect: first, leaving the determination of who is a journalist to officers on the protest’s ground level, with the decision being subject to a reasonableness standard; second, through a government credentialing process. Valeska concludes by summarizing what the right would accomplish. He argues for media exemptions from related curfew and equipment ordinances, heightened protections against arrest and detainment, and special access to spaces cleared by dispersal orders. This Article demonstrates that we are in a time of intensifying social unrest and that critical prophylactic steps must be taken to shore up protections for one of our most important democratic institutions.
Keywords: First Amendment; press; press clause; protest; protests; journalist; journalists; journalism; media